Obsessive compulsive disorder and obsessive beliefs - (:unkn) unknown (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2012)
Objective: Obsessive beliefs that the person has are gradually get important in the cognitive models of obsessive compulsive disorder (OCD). The cognitive interventions targeting these beliefs will increase the success of the treatment. Our study aims to evaluate the obsessive beliefs in patients with OCD and to compare them with the healthy people. Methods: One hundred and sixteen outpatients with OCD and 155 healthy volunteers were included in the study. Participants were evaluated with Obsessive Beliefs Questionnarie-44 (OBQ-44), Beck Depression Inventory and State Trait Anxiety Inventory. SPSS for Windows 13.0 statistical software was used for the statistical evaluation. Results: Total scores and subscale scores for OBQ-44 in the OCD group were found to be significantly higher than those in the control group. When state anxiety level was controlled, OBQ-44 'importance and control of thoughts' subscale and total scores were found not to be significant. When trait anxiety level and depression level were controlled, OBQ-44 total score and all subscale scores were found not to be significant. Conclusion: Obsessive beliefs were higher in the OCD patients, which may confirm the hypothesis, suggested by cognitive theories that certain obsessive beliefs are related to obsessive symptoms. It is determined that obsessive beliefs were not linked with the severity of the disease cross-sectional. Obsessive beliefs were found to be closely related to trait anxiety and depression. Because of this relation between obsessive beliefs and anxiety; it is thought that these beliefs maybe generally the consequences of anxiety. In order to determine the relation between general anxiety and obsessive beliefs, they should be investigated at other anxiety disorders and it would be useful to be compared with the OCD results. In order to investigate the change in obsessive beliefs with the treatment, prospective studies should be done. (Anatolian Journal of Psychiatry 2012; 13:91-96)
Keywords: obsessive compulsive disorder; obsessive beliefs; OBQ-44; OCD cognitive model; COGNITIVE THEORY; PERFECTIONISM; SPECIFICITY; DOMAINS; RESPONSIBILITY; QUESTIONNAIRE; SYMPTOMS; VERSION; OCD